Apreciación de los empleadores de las organizaciones del sector público del departamento del Quindío sobre la calidad de la formación y el desempeño de los egresados del programa de Contaduría Pública de la Universidad del Quindío (2014)
In the procedural development of this project is inevitable to be aware of the laws and regulations governing higher education in Colombia, in addition to the standards set quality standards in the academic processes of different institutions and regulatory watches, assessed and controlled educational procedures. Such is the case of Law 30 of 1992, which defines the character and autonomy of higher education institutions, the object of academic programs and promotion procedures, inspection and supervision of education; For its part, the quality conditions that higher education should be established by Decree 2566 of 2003 and Law 1188 of 2008, the decree regulated the conditions of quality and other requirements for the offering and development of academic programs in higher education , a standard that was repealed with the Law 1188 of 2008 establishing a mandatory quality conditions for the qualified academic program record for which the Institutions of Higher Education, in addition to demonstrating compliance with conditions of quality programs, certain conditions must express institutional quality, ie, these laws are intended to reach a comprehensive education to meet the needs of today's society that is becoming more demanding and progressive; also entities such as the National Accreditation Board, which is explained as a set of policies, strategies, processes and organizations whose main objective is to ensure that society's institutions of higher education that are part of the system meet the highest quality requirements and performing its aims and objectives. (Artículo 53 de la Ley 30 de 1992 ).